Vous êtes sur la page 1sur 3

Pure Mathematics – Calculus

p.1

King’s College 2007 – 2008 F.6 Pure Mathematics Revision Test 10 Suggested Solution

2
x
1 − t
2 dt
1.
Let
t =
tan
. Then,
cos
x =
and
dx =
.
2
2
2
1
+ t
1
+ t
⎛ x ⎞ ⎞ ⎟
⎜ ⎛ tan
dx
2
dt
2
2 1
2 ⎠
1
=
=
tan
⎛ ⎜ t
⎟ +
C =
+ C
2
2 + cos x
3 + t
3
3 ⎠
tan
3
(
)
2
ln tan 3
x
+
cos 4
x
3sec
x
4 sin 4
x
3
− 0
l
2.
(a)
lim tan 3 x
(
0
1 lim
lim
+
cos 4 x
)
x =
e
x
0
x =
e
x
0
tan 3
x
+ cos 4
x
=
e
0
+ 1
x →

=

e

3

(b) Note that
cos
2004
+
x
cos
x
=−
2sin
=− 2sin
So,
0 ≤
cos
2004
+
x
cos
x

2004 +
x +
x
2
2004 +
x +
x

2 sin

2

2004 +
x
x
2
1002
2004 +
x
+
x

for all x > 0.

sin

sin

1002
2004
+
x
+
x

Since

2

we have

1002
sin
2004 + x +
x
lim(cos
2004 +
x
x
→∞

0

cos

as

x → ∞ ,

x )= 0

(by Sandwich Theorem).

for all x > 0

Let
f (x ) = cos
x
for all x > 0.
Then,
f
' (
x =
)
. By Mean Value Theorem, for some ξ ∈ (x ,2004 + x ), we have
1002sin
ξ
cos
2004 + x − cos
x = f
(
2004 + x − f
)
()
x = 2004 f '
() ξ
= −
.
ξ
1
Note that
→ 0
as
ξ
→ ∞
and
sin
ξ
≤ 1
for all
ξ > 0 .
ξ
1002sin
ξ
Therefore,
→ 0
as
ξ → ∞ .
ξ
Further note that as
x → ∞ , ξ → ∞ .
Thus, we have
lim(cos
2004 +
x
− cos
)= 0
.
x
→∞

Pure Mathematics – Calculus

p.2

3.

3

sec θd θ =

So we have

sec 3

θθ

d

=

secθd tanθ = secθ tanθ

2

tan θ secθdθ = secθ tanθ

3

sec θdθ +

secθdθ

sec

θ

tan

θ

1

+

2

2

sec
θ
tan
θ
1
sec
θθ
d
=
+
ln
2
2

sec

θ

+

tan

θ

+ C , where C is a constant.

4. Note that

1

1 sin 1 for all x 0 .

x

So we have

sin x

sin

x sin

1
x

sin x

for all

x 0 .

Since

sin x

)

1

=

0

lim

(

=

0

=

lim sin x

, we have

lim sin

x

sin

(by Sandwich Theorem).

 x → 0 x → 0 x → 0 x Note that sin 1 x ≤ 1 for all x ≠ 0 and lim sin x = 0 . x → 0 Thus, we have lim sin x sin 1 = 0 x → 0 x

5. (a)

(b)

 (i) h( a) = f( a) – f ( a) – 0 = 0 h( b) = f( b) – f ( a) – ( f ( b) – f ( a)) = 0 (ii) By Mean Value Theorem, there exists β ∈ (a , b ) such that ( h β ' ) =

Now, we have

h

'

() ()

β = β

f

'

Since

g '(β ) 0 , thus we have

f

()

b

()

f a

g

()

b

()

g a

'()= 0

g β

 f ' () β = () () f b − f a g ' () g ()b g ()a β −

.

.

() ()

h b

h a

b a

= 0 .

Note that F and G are differentiable in R, G (x ) G (c ) and G '(t ) 0 for all t I .

By (a)(ii), there exists γ I

such that

F

'

()

γ

() ()

F c

F x

G

'

() G ()c G ()x

γ

=

.

However, F( x ) = u( x) – u( x ) – 0 = 0 and

(

G x

)

=

(

x

x

)

2

2

= 0 .

So, there exists γ I , such that

F

'

()

γ

()

F c

G

'

() G (c )

γ

=

.

Also, F ' (t ) = − u ' (t ) = u ' ' (t )(x

Moreover, G '(t ) = −(x t ). Therefore, we have F '()γ = −u ''(x γ ) and G '(γ ) = −(x γ ).

t ) + u ' (t ) = − u ' ' (x

t

) .

So we have

u

''

()(

γ

x

γ

)

(

x

γ

)

=

() () ()(

u x

u c

'

u c

x

c

)

(

x

c

)

2

2

.

Thus, we have

u

(

x = u c + u c x c +

)

( )

'

( )(

)

u ''

()

γ

2

(

x

c

) 2

.

Pure Mathematics – Calculus

p.3

(c)

(i)

v (0)

=

=

=

lim v x

⎝ ⎝

lim x

()

x

x

0

0

v x ⎞ ⎞

()

x

(

x

lim

0

)

x

lim

x

0

()

v x

x

= 0

(

since

v

is continuous at 0

)

(ii)

()

v ' 0

=

lim

x

0

() ()

v x

v 0

x 0

=

lim

x

0

()

v x

x

=

2006

Case 1:

x = 0

LHS = v (0) = 0

RHS = (2006)(0) + 0 2 = 0

So, the inequality holds for x = 0.

(by (c)(i))

Case 2:
x ≠ 0
Putting u = v and c = 0 in the latter result of (b), there exists
d ∈ ℜ
such that
v d
''
()
v d
''
()
() () ()
2
2
2
v x = v
0
+ v
' 0
x +
x
=
2006
x
+
x
2006
x
+
x
.
2
2
2
By combining the above two cases,
v
(
x ≥ 2006 x + x
)
for all
x ∈ℜ
.
Since v ''(t )≥ 2 for all t ∈ℜ , we hav e
Case 1:
x ≥ 0
∫ s
v
''
()
t dt
∫ s
2
dt
for all
s
0
0
0
v
'
() ()
s
v
' 0
2
s
v
'
()
s
2
s
+
2006
∫ x
v
'
()
s ds
∫ x
(
2
s
+
2006
)
ds
0
0
2
v
() ()
x
v
0
x
+
2006
x
v
()
2
x
2006
x
+
x
Case 2: x < 0
v ''(t )≥ 2
for all t ∈ℜ
∫ 0
v
''
()
t dt
∫ 0
2
dt
for all
s
0
s
s
v
' 0
() ()
v s
'
≥−
2
s
v
'
()
s
≥− s +
(
2
2006
)
∫ 0
v s ds
'
()
≥−
∫ 0
(
2
s
+
2006
)
ds
x
x
2
v
() ()
0
+
v x
x
+
2006
x
()
2
v
x
2006
x
+
x
()
2
By combining the above two cases,
v
x ≥ 2006 x + x
for all
x ∈ ℜ .